Epidemiology of chronic hepatitis B and C in Victoria, Australia: insights and impacts from enhanced surveillance - Jennifer H. MacLachlan; Nicole Romero; Nasra Higgins; Rachel Coutts; Rachel Chan; Nicola Stephens; Benjamin C. Cowie (Elsevier, 2020)
Abstract Objective: To assess the impact of an enhanced viral hepatitis surveillance program on data completeness and on epidemiological assessment of affected populations. Methods: Notified cases of non‐acute hepatitis B and C were analysed to determine demographic characteristics and risk factors during the period prior to July 2015-June 2016, and during enhanced surveillance of the period July 2016-June 2017, during which time doctors were contacted for information about new diagnoses. Results: During the enhanced period, completeness for country of birth and Indigenous status doubled for both hepatitis B and hepatitis C, from 18-37% to 48-65%. The incidence ratio of hepatitis C among Aboriginal and Torres Strait Islander people increased from eight‐fold to 11.4‐fold, and the proportion of hepatitis B cases reported as born in China and Vietnam relative to other countries increased. New data fields identified that 12% of hepatitis C diagnoses occurred in a correctional facility, and 2% of hepatitis B cases were healthcare workers. Conclusions: Improved data completeness highlighted the underlying epidemiology of chronic viral hepatitis, demonstrating the increased burden of infection among specific priority populations. Implications for public health: Enhanced surveillance provides greater insight into the epidemiology of chronic viral hepatitis, identifying groups at risk and opportunities for public health action.